Frequency of lettuce big-vein associated virus and mirafiori lettuce big-vein virus in symptomatic and assymptomatic lettuce plants and sap and soil transmission. - Sanches, Márcio Martinello [UNESP]; Krause-Sakate, Renate [UNESP]; Zerbini, Francisco Murilo; Rosales, Marlene; Le Gall, Olivier; Pavan, Marcelo Agenor [UNESP] (My University, 2007)
The occurrence of big vein disease symptoms and the association of Lettuce big-vein associated virus (LBVaV) and Mirafiori lettuce big-vein virus (MLBVV) was evaluated by RT-PCR using specific primers for both viruses. A total of 366 symptomatic plants were collected during June and September 2004 and during April and July 2005 at Bauru, Campinas and Mogi das Cruzes in São Paulo state, and 18 symptomless plants were collected in Mogi das Cruzes on December 2004. Mixed infection was detected in 76,2% of the symptomatic plants, 11,5% had only MLBVV and 6,6% had only LBVaV. In the symptomless plants collected in areas with high incidence of the disease throughout the winter, MLBVV was found in 9 plants and LBVaV in 7 plants. Four plants had both viruses, indicating that symptom development depends on abiotic factors, such as temperature. Plants with MLBVV and LBVaV (mixed infection) were used as source of virus in a host range assay at 16C/ 10°C (day/ night) and 11h light period. MLBVV was transmitted to Nicotiana tabacum TNN, N. rustica, N. occidentalis, Chenopodium quinoa and lettuce cv. Trocadero and White Boston, while LBVaV was transmitted only to lettuce cv. White Boston. No symptons could be verified for these plants with the exception of C. quinoa that showed local lesions. Transmission through soil in areas with high incidence of the disease was observed for LBVaV to lettuce cv. White Boston and MLBVV for lettuce cv. Trocadero and White Boston, but only cv. White Boston showed symptoms. Together, these results demonstrate the difficulties in transmitting both viruses, even under controlled laboratory conditions.
Frequência de lettuce big-vein associated virus e mirafiori lettuce big-vein virus em plantas de alface no estado de são paulo e transmissão através de extrato vegetal e solo
Keywords: Biological characterization; Ophiovirus; RT-PCR; Varicosavirus